2013
DOI: 10.1007/s11082-013-9802-1
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in soft-glass suspended core photonic crystal fiber

Abstract: Supercontinuum from 800 to 2,600 nm has been obtained in a soft glass suspendedcore photonic crystal fiber. The fiber has been fabricated using an in-house synthesized, lead-bismuth-galate oxide glass (PBG-08), which has a transmission window from 500 nm to 4,500 nm. Dispersion characteristic has been designed to enable efficient pumping in the anomalous regime, using typical telecommunication wavelengths and influence of discrepancy between design and physical dispersion profile of fiber is discussed. An opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Nevertheless, experimentally recorded supercontinuum spectrum -shown in Fig. 3b -under pumping with 70 fs pulses at 1550 nm reached a wavelength of 2600 nm for fiber sample length of just 5.5 cm [7].…”
Section: Supercontinuum Generation In Suspended Core Fibersmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, experimentally recorded supercontinuum spectrum -shown in Fig. 3b -under pumping with 70 fs pulses at 1550 nm reached a wavelength of 2600 nm for fiber sample length of just 5.5 cm [7].…”
Section: Supercontinuum Generation In Suspended Core Fibersmentioning
confidence: 96%
“…(a) (b) Figure 3: (a) SEM images of photonic structure of the developed suspended core photonic crystal fiber using PBG-08 glass; (b) Measured supercontinuum spectrum in the fiber [7].…”
Section: Supercontinuum Generation In Suspended Core Fibersmentioning
confidence: 99%
“…Solitons undergo Raman-induced frequency shift (RIFS) towards the longer ZDW soon after the fission and amplify dispersive wave (DW) generated across the longer ZDW by the phase matching condition. In [18], Klimczak et al experimentally demonstrated SC spreading from 0.8 μm to 2.6 μm by pumping in the anomalous dispersion region in a dispersion engineered lead-bismuth-galate oxide glass micronstructured fiber. Recently, nonuniform waveguides with continuously varying dispersion profiles have been designed to generate SC with wider bandwidth [9,11,14,19].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the pumping signal should be well confined in a small area in order to produce high power density with available pulse laser sources, which in turn magnify nonlinear effects. The aforementioned PCFs allow achieving energy density at the level well over 10 nJ/μm 2 [4], [5]. And last but not least, various effects that contribute to supercontinuum generation, such as self-phase modulation, soliton fission, Raman scattering or four-wave mixing, require appropriate spectral shape of mode dispersion, which can be controlled by the adjustment of photonic crystal cladding.…”
Section: Introductionmentioning
confidence: 99%